Palmitoylethanolamide (PEA) as a Potential Therapeutic Agent in Alzheimer’s Disease - Beggiato, Sarah; Tomasini, Maria Cristina; Ferraro, Luca (Frontiers in Pharmacology, 2019)
N-palmitoylethanolamide (PEA) is a non-endocannabinoid lipid mediator belonging to the class of the N-acylethanolamine and was firstly isolated from soy lecithin, eggs yolk and peanut meal. Either preclinical or clinical studies indicate that PEA is potentially useful in a wide range of therapeutic areas, including eczema, pain, and neurodegeneration. PEA containing products are already licensed for use in humans as a nutraceutical, a food supplement, or a food for medical purposes, depending on the country. PEA is especially used in humans for its analgesic and anti-inflammatory properties and demonstrated high safety and tolerability. Several preclinical in vitro and in vivo studies have proven that PEA can induce its biological effects by acting on several molecular targets in both central and peripheral nervous systems. These multiple mechanisms of action clearly differentiate PEA from classical anti-inflammatory drugs and attribute to the compound quite unique anti(neuro)inflammatory properties. According to this view, preclinical studies indicate that PEA, especially in micronized or ultramicronized forms (i.e. formulations which maximize PEA bioavailability and efficacy), could be a potential therapeutic agent for the effective treatment of different pathologies characterized by neurodegeneration, (neuro)inflammation and pain. In particular, the potential neuroprotective effects of PEA have been demonstrated in several experimental models of Alzheimer’s disease. Interestingly, a SPECT case study reported that a mild cognitive impairment (MCI) patient, treated for 9 months with ultramicronized-PEA/Luteolin, presented an improvement of cognitive performances. In the present review we summarized the current preclinical and clinical evidence of PEA as possible therapeutic agent in Alzheimer’s disease. The possible PEA neuroprotective mechanism(s) of action is also described.